The effect of withholding salt on growth and condition of beef cattle and on digestibility of feed constituents. - Smith, E.F.; Parrish, D.B. (Kansas Agricultural Experiment Station, 2012)
The first phase of this experiment pertaining to the effect of withholding salt on growth and condition of steer calves has been completed. The second phase dealing with the effect of withholding salt on the digestibility of the feed nutrients, is in progress. Twelve steer calves, six having free access to salt and six not having access to salt were wintered on bluestem pasture. Each lot received one and one-half pounds of soybean pellets per head daily. Prairie hay was fed when snow covered the grass.
Keywords: Beef; Salt; Growth; Digestibility